Thermoplastic polybutadiene elastomer and preparation method thereof
By introducing polyethylene block links and random links into polyethylene-1-butene thermoplastic elastomer, combined with anionic polymerization and titanium catalytic hydrogenation technology, polymers with thermoplastic elastomer properties were prepared, which solved the problem that the existing hydrocarbon polyolefin polymers did not have thermoplastic elastomer, and achieved good mechanical properties and thermal aging resistance.
Patent Information
- Application Number
- CN202311344757.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-17
- Publication Date
- 2025-04-18
AI Technical Summary
The existing hydrocarbon polyolefin polymers such as EPDM and POE do not have the behavior of thermoplastic elastomers, and their elasticity is poor, their modulus is high, and their hardness is high, and they are not suitable for use as elastic materials with low hardness.
A polyethylene-1-butene thermoplastic elastomer (PEBB) is used, and its molecular structure includes polyethylene block links and polyethylene/poly1-butene random links. It is prepared by anionic polymerization and titanium-catalyzed hydrogenation processes to control the block ratio and molecular mass distribution in the molecular structure to achieve the performance of the thermoplastic elastomer.
It achieves good flexibility, elasticity and tensile strength of the polymer, has the characteristics of good physical and mechanical properties and easy processing, and reflects excellent thermal aging resistance.
Smart Images

Figure CN119841992A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a thermoplastic polybutadiene elastomer, in particular to a polyethylene-1-butene rubber and a preparation method thereof, belonging to the technical field of new rubber materials. Background Art
[0002] Single polybutadiene belongs to diene rubber and does not belong to the technical category of thermoplastic elastomers. Polyethylene-1-butene random copolymer has no physical crosslinking nodes in its molecular structure and is not a thermoplastic elastomer. Only molecules containing highly crystalline segments and randomly distributed polyolefin chain segments have the behavior of thermoplastic elastomers. Existing commercially available polyolefin elastomers (POE) are copolymerized by ethylene and a small amount of 1-butene or 1-octene, and the α-olefin contained in its molecular structure is 10-15%. The presence of 1-butene or 1-octene chain segments in POE molecules destroys the regularity of polyethylene chains, but also gives the copolymer excellent transparency and good elasticity. At room temperature, the crystallization of polyethylene chains serves as physical crosslinking points, and the amorphous regions of random copolymer chains of ethylene-comonomers make the copolymer plastic. The insufficient molecular weight distribution makes POE have high tensile strength and impact resistance, and also shows good processing performance, but its disadvantages are high modulus, high hardness, poor resilience and high crystallinity, and incompatibility with mineral oil. It has been widely used in photovoltaic panels and blended with polyolefin resins, but it is not suitable for low hardness elastic materials. In addition, CA10A and CA10A launched by Lyondebasell belong to thermoplastic polyolefin (TPO), which has high strength, high modulus, high elongation and good flexibility. It is an alloy material with an "island" structure formed by blending hydrocarbon rubber and polypropylene.
[0003] Traditional commercially available carbon-hydrogen rubbers such as ethylene-propylene rubber (EPDM) are copolymerized by ethylene, propylene and dienes. According to their different molecular structure characteristics, there are more than 20 types of applications. The EPDM ethylene-propylene ratio can be changed during the polymerization stage. When the EPDM ethylene-propylene ratio changes from 50 / 50 to 80 / 20, the positive effects include: higher green strength, tensile strength, crystallinity and glass transition temperature, the ability to convert the raw material polymer into granules, and better extrusion properties. Negative effects: worse calendering mixing, low temperature properties and compression deformation, etc.
[0004] There are 19 types of EPDM currently on the market launched by DOW Chemical, 13 of which are semi-crystalline polymers with a crystallization temperature of 33 to 46°C. Although the polymer has a large deformation below the crystallization temperature, it still exhibits a high tensile strength. The comprehensive physical properties of this type of polymer decrease with the increase of room temperature. It is not a thermoplastic elastic material. If the vulcanization process is not carried out, the raw rubber should not be used directly. It has commercial value only after vulcanization and molding.
[0005] In summary, existing hydrocarbon polyolefin polymers such as EPDM and POE do not have the behavior of thermoplastic elastomers, and thermoplastic hydrocarbon elastomers with excellent comprehensive properties have not yet been reported in the literature. Summary of the invention
[0006] Existing hydrocarbon polyolefin polymers such as EPDM and POE do not have defects such as poor thermoplastic elasticity and resilience.
[0007] The first object of the present invention is to provide a polyethylene-1-butene thermoplastic elastomer (PEBB) having polyethylene block segments, which has two block segments of polyethylene segments and polyethylene / poly-1-butene random segments, exhibits good flexibility, elasticity and tensile strength, can be used as a polyolefin thermoplastic elastomer, has the characteristics of good physical and mechanical properties, easy processing, etc., and more importantly, also exhibits excellent heat aging resistance.
[0008] The second object of the present invention is to provide a method for preparing polyethylene-1-butene thermoplastic elastomer, which is simple, low-cost, can be produced using existing mature equipment and processes, and is easy to industrialize.
[0009] In order to achieve the above technical objectives, the present invention provides a thermoplastic polybutadiene elastomer having the following molecular structure:
[0010]
[0011] in,
[0012] x, y, a and b are the degrees of polymerization;
[0013] x+y=440~800;
[0014] a+b=1100~2500;
[0015] x / (x+y)<0.05;
[0016] a / (a+b)=0.15~0.70.
[0017] The PEBB molecule of the present invention comprises two polybutadiene blocks with different microstructures, wherein the first block is a block mainly composed of a 1,4-polymer structure of butadiene, i.e., a polyethylene block, wherein the 1,4-polymer structure accounts for more than 95% and is easy to crystallize, has hard segment properties, can provide physical cross-linking points for the polymer, and gives the polymer high tensile strength and modulus, while the second block is a copolymer block of randomly distributed butadiene 1,2-polymer structure and 1,4-polymer structure, which has soft segment properties, giving the polymer good flexibility and elasticity, so that the entire molecule exhibits the behavior of a thermoplastic elastomer.
[0018] The ratio of the first block to the second block in the PEBB molecule of the present invention should be controlled within an appropriate ratio range. If the ratio of the first block (polyethylene block) is too low, the crystallinity of the polymer is too low, the tensile strength of the polymer is too low, and the heat resistance is poor; if the polyethylene block ratio is too high, the crystallinity of the polymer is too high, the solubility of the hydrogenated polymer in the cyclohexane solvent is poor, and it solidifies at a low temperature of 40°C, which is not conducive to mass transfer and heat transfer in subsequent processing operations.
[0019] The 1,2-addition units and 1,4-addition units in the second block of the PEBB molecule of the present invention are randomly distributed, and the ratio of the 1,2-addition units must reach a certain ratio to ensure that the PEBB polymer has appropriate flexibility or elasticity.
[0020] As a more preferred solution, in the molecular structure of the thermoplastic polybutadiene elastomer, a / (a+b)=0.20-0.30. An appropriate amount of 1,2-addition units produces short chain branches, which can reduce the crystallinity of PEBB and ensure that PEBB has appropriate flexibility or elasticity.
[0021] As a preferred embodiment, the number average molecular weight of the thermoplastic polybutadiene elastomer is 8×10 4 ~16×10 4 , the molecular weight distribution index is M w / M n =1.05~1.15. The thermoplastic polybutadiene elastomer of the present invention has a low-middle molecular weight and a narrow molecular fraction, and has a large melt index (MFR), is easy to be injection molded and formed by film drawing, and has good processing performance; while the polymer with too high molecular weight has poor processing performance, and the surface of the prepared elastic film will have defects and the surface is not smooth. In addition, it is easy to control the polymer with a narrow molecular fraction prepared by anionic polymerization, and at the same time, the oil filling rate of the polymer with less side ethyl content is low, and oil seepage is easy to occur. The molecular weight distribution is too wide, there are more low molecular components, the polymer crystallization temperature is low, and the strength is poor.
[0022] As a preferred solution, the thermoplastic polybutadiene elastomer has a crystallinity of 25-40% and a crystallization temperature Tc =50~90℃, melt index MFR 200 ℃ / 5kg =0.5~7.5g / 10min.
[0023] The present invention also provides a method for preparing a thermoplastic polybutadiene elastomer, which comprises heating an anionic polymerization system containing an activator to 85-95°C, adding an initiator and butadiene to initiate and carry out a first-stage polymerization, then cooling the anionic polymerization system to 50-65°C, adding butadiene to carry out a second-stage polymerization, and after the second-stage polymerization is completed, the obtained rubber solution is subjected to a catalytic hydrogenation reaction using a titanocene catalyst system to obtain the elastomer.
[0024] As a preferred solution, the anionic polymerization system uses cyclohexane as a solvent.
[0025] As a preferred solution, the amount of the solvent is measured based on a mass fraction of the total mass of butadiene in the solvent of 10 to 14%.
[0026] As a preferred embodiment, the activating agent is tetrahydrofuran.
[0027] As a preferred solution, the amount of the activator is measured at a concentration of 10 to 20 mg / kg in the solvent. It is worth further explaining that: it is well known that tetrahydrofuran (THF) is a commonly used activator for anionic polymers such as styrene-butadiene polymers (SBS). THF is greatly affected by polymerization temperature. For example, the higher the polymerization temperature, the lower the content of 1,2-structural units in the butadiene polymer chain; the lower the polymerization temperature, the higher the content of 1,2-structural units. In the present invention, high-temperature polymerization is used in the first stage of polymerization to produce more 1,4-structural units, which is convenient for producing longer polyethylene blocks after hydrogenation. Low-temperature polymerization is used in the second stage to produce more 1,2-structural units, which is convenient for producing more ethyl side chains after hydrogenation, increasing the disordered distribution of hydrogenated polyethylene and poly-1-butene and the elasticity of the entire polymer.
[0028] As a preferred solution, the polymerization time is not less than 20 minutes. The polymerization temperature is 85-95°C, and the polymerization time is not less than 20 minutes to ensure that B 1 The 1,4-addition unit content in the segment is >95%, and the 1,2-addition unit content is <5%, or even lower, which is beneficial to the formation of regular block crystalline chains of polyethylene after hydrogenation and improves the tensile strength and crystallization temperature of PEBB polymers.
[0029] As a preferred solution, the second stage polymerization time is not less than 40 minutes. The temperature of the second stage polymerization is a low temperature condition of 50 to 65°C, and the second stage polymerization time is not less than 40 minutes to ensure B 2The 1,4-addition unit content is 30-85%, and more preferably 70-80%; the 1,2-addition unit content is 15-70%, and more preferably 20-30%. The 1,4-addition and 1,2-addition units are preferably randomly arranged to ensure that the PEBB polymer has suitable flexibility or elasticity.
[0030] As a preferred solution, the conditions of the catalytic hydrogenation reaction are: alkyl lithium as an activator, a mixture of dimethyl phthalate and methyl o-toluate as a co-catalyst, dicyclopentadiene titanium dichloride as a main catalyst, a hydrogen pressure of 13 to 16 bar, a temperature of 75 to 110° C., and a hydrogenation time of not less than 120 min. Alkyl lithium is, for example, n-butyl lithium.
[0031] As a more preferred solution, the dosage of the main catalyst is (0.04-0.06) g / 100 g polymer; the dosage of the co-catalyst is 1 / 5-1 / 8 times the molar amount of the main catalyst; the dosage of the activator is 6-10 times the molar amount of the co-catalyst. Under the preferred catalytic hydrogenation conditions, the hydrogenation degree of the polymer can be guaranteed to be 99.0-99.50%.
[0032] The preparation method of PEBB provided by the present invention is specifically as follows:
[0033] The first step is to heat the anionic polymerization system containing the activator to 85-95°C, then add a certain amount of n-butyl lithium (NBL), and then add a certain amount of butadiene to carry out homopolymerization for 20-25 minutes to form B 1 -Li + The active polymer, B 1 It is mainly 1,4-addition of butadiene, and also contains a small amount of 1,2-addition units, among which the number of 1,4-addition units is much greater than that of 1,2-addition.
[0034] Step 2: Cool the above polymerization solution, add a certain amount of butadiene and react at 50-65°C for not less than 40 minutes. The resulting polymer exhibits B 1 -B 2 -Li + Active polymer (BR original rubber), B 2 The segment contains a higher proportion of 1,2-addition units.
[0035] Step 3: Add a certain amount of NBL, co-catalyst and titanocene catalyst into the BR glue solution and react at a certain temperature and hydrogen pressure for not less than 120 minutes to obtain the PEBB glue solution.
[0036] Step 4: Wash and terminate the PEBB glue with a small amount of aqueous solution of tert-decanoic acid, remove volatiles through a twin-screw extruder, extrude, and pelletize to obtain PEBB pellets.
[0037] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0038] The PEBB of the present invention can be prepared by using existing mature anionic polymerization and titanocene catalytic hydrogenation processes. The preparation process belongs to homogeneous reaction, the method is simple, and the existing mature process can be used for synthesis, which is easy to control and industrialize.
[0039] The PEBB of the present invention can effectively control the diblock polyethylene chain segments and polyethylene / poly-1-butene random chain segments in the polymer by using THF with weak regulating ability as a microstructure regulator and high-low temperature swing polymerization technology, thereby giving the polymer good flexibility, elasticity and tensile strength, and can be used as a polyolefin thermoplastic elastomer. It has the characteristics of good physical and mechanical properties and easy processing, and more importantly, also exhibits excellent heat aging resistance.
[0040] The PEBB of the present invention can be used alone or blended with polyolefin resin or vulcanized by peroxide to prepare elastic alloy, and can be formed by extrusion or stretching, showing excellent processing performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 Example 1 Polymer B 1 -B 2 -GPC spectrum of 1# original rubber.
[0042] Figure 2 Example 1 Polymer B 1 -B 2 -1# original rubber H 1 -NMR.
[0043] Figure 3 Example 1 hydrogenated polymer PEBB-1#H 1 -NMR. DETAILED DESCRIPTION
[0044] The following examples are intended to further illustrate the present invention in detail and are not intended to limit the scope of protection of the claims of the present invention.
[0045] In the following examples, the number average molecular weight and molecular weight distribution index of the polymers were determined by gel permeation chromatography (GPC); 1 -NMR spectroscopy is used to quantitatively determine the microstructure of the polymer; the crystallinity of the hydride is determined by differential scanning calorimetry (DSC) analyzer; the mechanical properties of the raw rubber are tested according to the GB / T36089-2018 method.
[0046] Example 1
[0047] In a 5-liter polymerization kettle under nitrogen protection, 3500 mL of cyclohexane and 0.04 mL of tetrahydrofuran (THF) were added in sequence, and the temperature was raised to 85°C with hot water. Then, 5.0 mL of 0.5 mol / L NBL and 100 mL of the first butadiene were added, and the polymerization was carried out at a nitrogen pressure of 4.0 bar for 25 minutes. Then, the temperature of the polymerization kettle was lowered to 50°C, and 260 mL of the second butadiene was added, and the polymerization was carried out at a temperature not exceeding 65°C for 40 minutes. BR raw rubber was obtained. 1 -NMR and GPC spectra are shown in Figure 1 and Figure 2 .
[0048] 4 mL of 0.5 mol / L NBL, 3.5 mL of 0.02 mol / L cyclohexane solution of dimethyl phthalate and methyl o-toluate (molar ratio 1:1), and 0.16 g of dicyclopentadiene titanium dichloride were added to the BR glue, and the mixture was stirred and hydrogenated for 120 min at a hydrogen pressure of 14 bar and a temperature of 100°C to obtain a PEBB glue. The hydrogenated glue was then stirred and terminated with 30 mL of 10% tert-decanoic acid and 80 mL of water. After centrifugal dehydration, the glue was dry-dried in a twin-screw extruder to remove the solvent and a small amount of water. After underwater pelletization, PEBB transparent pellets (labeled as PEBB-1, the degree of hydrogenation of the polymer was measured to be 99.12% (moL), and the nuclear magnetic hydrogen spectrum was shown in FIG. Figure 3 , the characteristic behaviors of the polymers are shown in Tables 1 and 2.
[0049] Example 2
[0050] The relevant process conditions in Example 1 were kept unchanged, except that the amount of NBL used in the polymerization reaction was changed to 4.5 mL, and the amount of butadiene used in the first and second reactions was 130 mL and 270 mL, respectively.
[0051] Results The prepared polymer was designated as PEBB-2, and its behavior parameters are shown in Tables 1 and 2.
[0052] Example 3
[0053] The relevant process conditions in Example 1 were kept unchanged, except that the amount of NBL used in the polymerization reaction was changed to 3.5 mL, the amount of THF used was changed to 0.08 mL, and the amount of butadiene used in the first and second reactions was 135 mL and 300 mL, respectively.
[0054] Results The prepared polymer was designated as PEBB-3, and its behavior parameters are shown in Tables 1 and 2.
[0055] Example 4
[0056] The relevant process conditions in Example 1 were kept unchanged, and only the amount of NBL used in the polymerization reaction was changed to 4.0 mL.
[0057] Results The prepared polymer was designated as PEBB-4, and its behavior parameters are shown in Tables 1 and 2.
[0058] Example 5
[0059] As a control:
[0060] The relevant process conditions in Example 3 were kept unchanged, and only the amount of THF was changed to 0.12 mL.
[0061] Results The prepared polymer was designated as PEBB-5, and its behavior parameters are shown in Tables 1 and 2.
[0062] Example 6
[0063] As a control:
[0064] The relevant process conditions in Example 4 were kept unchanged, and only the amount of THF was changed to 0.02 mL.
[0065] Results The prepared polymer was designated as PEBB-6, and its behavior parameters are shown in Tables 1 and 2.
[0066] Example 7
[0067] As a control:
[0068] The relevant process conditions in Example 3 were kept unchanged, and only the amount of NBL used in the polymerization reaction was changed to 3.0 mL.
[0069] Results The prepared polymer was designated as PEBB-7, and its behavior parameters are shown in Tables 1 and 2.
[0070] Example 8
[0071] As a control:
[0072] The relevant process conditions in Example 1 were kept unchanged, and only the amount of NBL used in the polymerization reaction was changed to 6.3 mL.
[0073] Results The prepared polymer was designated as PEBB-8, and its behavior parameters are shown in Tables 1 and 2.
[0074] Table 1 Characteristic analysis of original rubber BR and hydrogenated rubber PEBB in the examples
[0075]
[0076]
[0077] Note: Melt index: tested at 200℃ / 5kg.
[0078] Table 1 Physical and mechanical properties of PEBB in the examples
[0079]
Claims
1. A thermoplastic polybutadiene elastomer, characterized in that: It has the following molecular structure: in, x, y, a and b are the degrees of polymerization; x+y=440~800; a+b=1100~2500; x / (x+y)<0.05; a / (a+b)=0.15~0.
70.
2. A thermoplastic polybutadiene elastomer according to claim 1, characterized in that: In the molecular structure of the thermoplastic polybutadiene elastomer, a / (a+b)=0.20-0.
30.
3. A thermoplastic polybutadiene elastomer according to claim 1, characterized in that: The number average molecular weight of the thermoplastic polybutadiene elastomer is 8×10 4 ~16×10 4 , the molecular weight distribution index is M w / M n =1.05~1.
15.
4. A thermoplastic polybutadiene elastomer according to any one of claims 1 to 3, characterized in that: The thermoplastic polybutadiene elastomer has a crystallinity of 25-40% and a crystallization temperature T c =50~90℃, melt index MFR 200 ℃ / 5kg =0.5~7.5g / 10min.
5. The method for preparing a thermoplastic polybutadiene elastomer according to any one of claims 1 to 4, characterized in that: The anionic polymerization system containing an activator is heated to 85-95°C, an initiator and butadiene are added to initiate and carry out a first-stage polymerization, then the anionic polymerization system is cooled to 50-65°C, butadiene is added to carry out a second-stage polymerization, and after the second-stage polymerization is completed, the obtained rubber solution is subjected to catalytic hydrogenation reaction using a titanocene catalyst system to obtain the obtained rubber.
6. The method for preparing a thermoplastic polybutadiene elastomer according to claim 5, characterized in that: The anionic polymerization system uses cyclohexane as a solvent; The amount of the solvent is measured based on the mass fraction of the total mass of butadiene in the solvent being 10-14%.
7. The method for preparing a thermoplastic polybutadiene elastomer according to claim 5, characterized in that: The activating agent is tetrahydrofuran; The dosage of the activator is measured based on the concentration of the activator in the solvent being 10 to 20 mg / kg.
8. The method for preparing a thermoplastic polybutadiene elastomer according to claim 5, characterized in that: The polymerization time is not less than 20 minutes; The time of the second stage polymerization is not less than 40 minutes.
9. The method for preparing a thermoplastic polybutadiene elastomer according to claim 5, characterized in that: The conditions of the catalytic hydrogenation reaction are: alkyl lithium as an activator, a mixture of dimethyl phthalate and methyl o-toluate as a co-catalyst, dicyclopentadiene titanium dichloride as a main catalyst, a hydrogen pressure of 13-16 bar, a temperature of 75-110° C., and a hydrogenation time of not less than 120 minutes.
10. The method for preparing a thermoplastic polybutadiene elastomer according to claim 9, characterized in that: The dosage of the main catalyst is (0.04-0.06) g / 100 g polymer; The amount of the co-catalyst is 1 / 5 to 1 / 8 times the molar amount of the main catalyst; The amount of the activator used is 6 to 10 times the molar amount of the co-catalyst.